Proposta de um modelo para a adequação dos sistemas de medição de desempenho aos níveis de maturidade da gestão da cadeia de suprimentos - Frederico, Guilherme Francisco (Universidade Federal de São Carlos, 2012)
ABSTRACT Supply chains are becoming increasingly important for companies to survive in today's competitive market. Theories and methods that contributing to the improvement of its management are important elements for research and development in the field of Industrial Engineering. Considering the performance measurement systems as one of these elements, this thesis aims to propose an adequacy model of performance measurement systems and its maturity to the maturity levels of supply chain management due to the lack of a study that shows the relationship between these two elements. For this were studied the performance measurement systems and its maturity as well as the maturity models for supply chain management enabling to build a theoretical model of relationship between these two elements. Using the multiple case method applied on three different analyze units it was possible to analyze the theoretical model purposed. As the main results of this research, in most of cases, was identified the existence of a relationship between the maturity of performance measurement system and maturity of supply chain management, although not always all elements of maturity of these two elements are in the same level of development. As contribution, this model aims to present a new approach to the theory of the performance measurement systems in the supply chain management, as well as, to provide to the practitioners the correct alignment between the maturity of supply chain management and maturity of performance measurement systems.
Keywords: Engenharia de produção; Maturidade; Sistema de medição de desempenho; Gestão da cadeia de suprimentos; Supply chain management; Performance measurement systems and maturity of supply chain management and maturity of performance measurement system.; ENGENHARIAS::ENGENHARIA DE PRODUCAO